High-activity Classical and Alternative Complement Pathway Genotypes-Association With Donor-specific Antibody-triggered Injury and Renal Allograft Survival - Mező, Blanka; Reindl-Schwaighofer, Roman; Eskandary, Farsad; Heinzel, Andreas; Wahrmann, Markus; Doberer, Konstantin; Heilos, Andreas; Bond, Gregor; Kläger, Johannes; Kozakowski, Nicolas; Haslacher, Helmuth; Oberbauer, Rainer; et al. (Transplantation direct, 2020)
BACKGROUND: Complement may contribute to donor-specific antibody (DSA)-triggered transplant injury. Here, we investigated whether the intrinsic strength of classical pathway and alternative pathway (AP) relates to the pathogenicity of DSA. METHODS: Classical pathway and AP high-activity genotypes were defined according to C4 gene copy number and the presence of functional polymorphisms in C3 (C3102G), factor B (fB32R), and factor H (fH62V) genes. Associations of these genotypes with blood complement profiles and morphologic/molecular rejection features were evaluated in a cohort of 83 DSA-positive patients (antibody-mediated rejection [AMR], n = 47) identified upon cross-sectional screening of 741 kidney allograft recipients ≥180 days posttransplantation. Associations with long-term graft survival were evaluated in a larger kidney transplant cohort (n = 660) not enriched for a specific type of rejection. RESULTS: In the cohort of DSA-positive subjects, the number of C4 gene copies was related to C4 protein levels in serum and capillary C4d staining, but not AMR activity. Patients with a high-activity AP complotype, which was associated with complement consumption in serum, showed enhanced microcirculation inflammation (median glomerulitis plus peritubular capillaritis score, 2 [interquartile range, 0-4 versus 1 0-2]; P = 0.037). In the larger transplant cohort, this complotype was associated with a slightly increased risk of graft loss (hazard ratio, 1.52; 95% confidence interval, 1.02-2.25; P = 0.038 and multivariable Cox model, 1.55; 1.04-2.32; P = 0.031). CONCLUSIONS: Our study suggests a contribution of complement genetics to the phenotypic presentation of AMR. Future studies will have to clarify whether a possible association of AP strength with graft survival relates to enhanced antibody-triggered injury.